Strategi Branding Produk Toko Souvenir Solo Melalui Media Sosial Tik Tok - Ardyansyah, Reza Dony; Sarjono, Herning Suryo; Sihabuddin, Sihabuddin (Solidaritas, 2024)
Along with the times the business market in Indonesia is experiencing increasingly fierce competition, the Solo Souvenir shop is branding Solo Souvenir Products through Tik Tok Social Media against the background of many companies that have made Tik Tok social media a place to introduce and develop their products, the purpose of this research is that the author is interested in examining how the branding strategy of Solo souvenir products through Tik Tok social media so that he can find out the branding strategy and provide additional insight and knowledge in branding strategies in Tik Tok media in the field of Communication Science and make references to other researchers regarding branding strategies in the marketing world. The results showed that the branding strategy carried out by Souvenir Solo through Tik Tok social media uses Keprefer's theory in (Konecnik & Go, 2013) introducing a hexagonal-shaped model, or prism brand identity, which is based on six main elements, namely the first brand identity physique (physical) with everything that characterizes Souvenir Solo. Second Personality (personality) which is based on the perception of consumer requests that describe the theme of the event. Third culture (culture) in the logo or motif there are cultural elements that can signify ownership. Fourth relationship (relationship) existing relationships or media partners such as companies, vendors, Wedding Organizer (WO). Fifth reflection or image (reflection or image) visual image of symbols, logos, names. Sixth self-image (self-image) Good reputation, or customer perception seems good and satisfied with the results of the products ordered at Souvenir Solo. suggestions given by researchers to Souvenir Solo, namely in marketing relationships carried out by solo souvenir shops, it is hoped that they can maintain the services provided and the quality and quantity that have been provided.